Anti-epileptic properties of terpineol extracted from Myristica fragrans Houtt. essential oil in the epileptic rat model. - Abdul Rahman, Mohd Amir Asyraf; Mohd Noor, Mohd Hezmee; Mustafa, Mohd Zulkifli; Islam, Rafiqul (2011)
Epilepsy is the manifestation of the disease due to overstimulation of the brain. The common signs of this disease are chronic, episodic and recurrent seizures. This problem usually occurs in dogs and cats with the prevalence of the problem estimated about 5.0-5.7 % in dog population and about 0.5 % in the cat population. Today, there is a lot of studies that had been done to search for the new alternative anticonvulsant and antiepilleptic using allopathy or traditional medicine, one of them that had been done was Myristica fragrans Houtt. The volatile oil from the Myristica fragrans Houtt. had been studied and proven to have anticonvulsant effect and one of the constituents suspected to contribute to the anticonvulsant activity was terpineol. This study was done to screen the anti-epileptic effect of terpineol that had been extracted from Myristica fragrans Houtt, essential oil to the kainic acid induced epileptic rat model by determining the effect of terpineol to the behavioural seizure activity and electroencephalogram (EEG) of this model. In this study, 3 adult male SpraqueDawley rats were established with a radiotelemetry system by implanting with electroencephalogram telemetry device and were induced for epilepsy using kainic acid and then treated with the terpineol with doses fo 20 mg/kg and 50 mg/kg. The rats were observed for behavioral seizure activity and electroencephalograms were done qualitatively and quantitatively based on the Racine Scale and EEG semiology. The results of this experiment indicated that terpineol had the antiepileptic properties by inhibiting the behavioral seizure activity and seizure electroencephalogram. The effect of antiepileptic of terpineol also correlated with the doses that were used in this experiment. The possible mechanism of antiepileptic effect of terpineol is by enhancing the gamma-aminobutyric acid (GABA) inhibition mechanism.